1986
DOI: 10.1161/01.res.58.5.706
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic interactions and mutual synchronization of sinoatrial node pacemaker cells. A mathematical model.

Abstract: Dynamic interactions and mutual entrainment of coupled sinoatrial pacemaker cells with different intrinsic frequencies were investigated using a computerized mathematical model. Transmembrane potentials were simulated using equations of individual membrane currents based on voltage clamp data for the sinoatrial node. The intrinsic frequency of a given cell was altered by applying bias hyperpolarizing current, or by changing the amount of slow inward current. Cells were coupled through simple ohmic resistances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 40 publications
2
37
1
Order By: Relevance
“…Previous studies have explored coupling inhomogeneity between simulated SAN cells and observed trends of synchronous firing and heterogeneous tissue becoming homogeneous through a democratic entrainment process at sufficient coupling values [20,32,33]. Our studies also support the theory of a democratic entrainment process both at the level of two coupled cells (Figure 6) where both cells adjusted their transmembrane dynamics to adjust to a new value that was distinct from firing alone.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Previous studies have explored coupling inhomogeneity between simulated SAN cells and observed trends of synchronous firing and heterogeneous tissue becoming homogeneous through a democratic entrainment process at sufficient coupling values [20,32,33]. Our studies also support the theory of a democratic entrainment process both at the level of two coupled cells (Figure 6) where both cells adjusted their transmembrane dynamics to adjust to a new value that was distinct from firing alone.…”
Section: Discussionsupporting
confidence: 85%
“…This further supports the idea that coupling non-linearly alters the ability of SAN cells to fire synchronously. In previous work, Michaels et al examined the effects of cellto-cell coupling strength on entrainment [20,33]. They tested both paired cells as well as small grids.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated by Jalife et al 48 and others, 24,49,50 interactions among a group of pacemaker cells result in a dominant pacemaker region. These interactions are electrotonic and involve mutual alterations in diastolic or pacemaker potentials, such that slower cells modulate faster cells to decrease their diastolic potentials and decrease their firing intervals and vice versa.…”
Section: Discussionmentioning
confidence: 92%
“…To adjust T, 10 we added a voltage and time-independent current to the time-independent current I L . 1>10 We have shown experimentally in anesthetized dogs that this model of the sinus node 7 -9 predicts quantitatively the dependence of SCL on [ACh].…”
mentioning
confidence: 99%